2015
DOI: 10.1158/1535-7163.mct-14-0883
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Screen Identifies a Potent Small Molecule Inhibitor of Stat5a/b with Therapeutic Potential for Prostate Cancer and Chronic Myeloid Leukemia

Abstract: Bypassing tyrosine kinases responsible for Stat5a/b phosphorylation would be advantageous for therapy development for Stat5a/b-regulated cancers. Here, we sought to identify small-molecule inhibitors of Stat5a/b for lead optimization and therapy development for prostate cancer (PC) and Bcr-Abl-driven leukemias. In silico screening of chemical structure databases combined with medicinal chemistry was used for identification of a panel of small-molecule inhibitors to block SH2-domain-mediated docking of Stat5a/b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 48 publications
1
68
0
Order By: Relevance
“…Based on these findings, we assessed the reliance of Phþ ALL cells on STAT5 activity by ex vivo and in vivo assays using IST5-002, a small molecule inhibitor of STAT5A/B tyrosine phosphorylation and dimerization, recently identified through structure-based in silico screening of compounds binding to the STAT5 SH2 domain (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these findings, we assessed the reliance of Phþ ALL cells on STAT5 activity by ex vivo and in vivo assays using IST5-002, a small molecule inhibitor of STAT5A/B tyrosine phosphorylation and dimerization, recently identified through structure-based in silico screening of compounds binding to the STAT5 SH2 domain (31).…”
Section: Discussionmentioning
confidence: 99%
“…In silico screening of chemical structure databases has recently identified IST5-002 as a candidate small molecule inhibitor of STAT5 (31). Such activity was confirmed based on its ability to suppress JAK2 and BCR-ABL1-mediated STAT5 phosphorylation, STAT5A/B dimerization, and to inhibit the transcriptional activity of STAT5A and STAT5B (31).…”
Section: Pharmacologic Inhibition Of Phospho-stat5 Suppresses Phþ Allmentioning
confidence: 96%
“…In 2015, Liao et al conducted a large scale structure-based virtual screening campaign for STAT5A/B inhibitors [99]. Using a STAT3 based homology model of STAT5, the authors docked 30 million compounds to the dimerization interface on the SH2 domain [65].…”
Section: Stat5 Inhibitorsmentioning
confidence: 99%
“…Although varied techniques have been reported that include full submersion of the tissue, the use of various scaffolds or supports is more effective where tissues are kept in contact with the media on agar or other metal grids made of titanium (McMahon et al 1972) or stainless steel (Nevalainen et al 1993). The grid approach was used to yield novel information such as the role of Jak2/Stat5a signaling to induce epithelial-to-mesenchymal transition and stemlike properties in prostate cancer (Gu et al 2013;Liao et al 2015;Talati et al 2015). With the development of bioengineered scaffolds to support and seed human cells for tissue regeneration, it is likely that these grid supports will lead to further advances as discussed below.…”
Section: Patient-derived Explants (Pdes)mentioning
confidence: 99%